2015
DOI: 10.1139/cjb-2014-0238
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat associations of lichens, feathermosses, and vascular plants in a caribou winter range, and their implications for understory development

Abstract: Vegetation-environment relationships are well understood for boreal lichen woodlands, but the mechanistic basis for small-scale understory patchiness (patches dominated by lichen, mosses, and vascular plants), and its implications for the prevalence of niche vs. neutral processes driving understory development, have not been explored. We asked whether predictable vegetation-environment associations exist at the microsite scale, with the goal of informing caribou range management. We sampled canopy and edaphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 68 publications
(81 reference statements)
4
24
0
Order By: Relevance
“…Overall, because we did not find any difference in the geochemistry and texture of the C horizon between ecosystem types and because our sites developed from surficial deposits (undifferentiated till, dead-ice moraine) of similar origin (glacial), our results, which are in line with those of other studies, suggest a biological influence of vegetation on soil profile development and soil chemistry (Finzi et al, 1998;Haughian and Burton, 2015;Wood et al, 1984). Haughian and Burton (2015) showed that more variability in soil composition could be explained by vegetation functional groups (e.g.…”
Section: Biological Influencesupporting
confidence: 90%
See 4 more Smart Citations
“…Overall, because we did not find any difference in the geochemistry and texture of the C horizon between ecosystem types and because our sites developed from surficial deposits (undifferentiated till, dead-ice moraine) of similar origin (glacial), our results, which are in line with those of other studies, suggest a biological influence of vegetation on soil profile development and soil chemistry (Finzi et al, 1998;Haughian and Burton, 2015;Wood et al, 1984). Haughian and Burton (2015) showed that more variability in soil composition could be explained by vegetation functional groups (e.g.…”
Section: Biological Influencesupporting
confidence: 90%
“…Haughian and Burton (2015) showed that more variability in soil composition could be explained by vegetation functional groups (e.g. mosses vs. lichens) than by abiotic characteristics (soil texture, topography).…”
Section: Biological Influencementioning
confidence: 99%
See 3 more Smart Citations